(3GdSdhc GdELQGej GdLfSj (B: s (3efaP Edi GdEQLGe GdLfSj(B-(3GdLQGFe GdLfSjI HGdEJaGb(B-(3GdLQGFe GdLfSjI HGdEQGOI GdefaQOI(B-(3LQGFe LfSjI eSJMOKI(B-(3LQGFe bOjeI fQi VQhQI EOQGLgG Vef GdLQGFe GdLfSjI (B((3LQjeI GdbPa(B) /s - (3fHjg, fSQjf YHO GdMejOs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2023)
(3jJfGhd cJGH (B((3GdSdhc GdELQGej GdLfSj(B) (3hGdPj bGe HJCdjag (B((3fSQjf YHO GdMejO fHjg(B) (3aj MhGdj (B(357) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdLQGFe GdLfSjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdJegjOj (B: (3efaP Edi GdELQGe GdLfSj, GdaUd GdChd (B: (3GdLQGFe GdLfSjI HGdEJaGb, GdaUd GdKGfj (B: (3GdLQGFe GdLfSjI HGdEOGQI GdefaQOI, GdaUd GdKGdK (B: (3LQGFe LfSjI eSJMOKI, GdaUd GdQGHY (B: (3LQGFe bOjeI fQi VQhQI EOQGLGgG Vef GdLQGFe GdLfSjI (B((3LQjeI GdbPa(B).s
(3HHdjhLQGajI (B: (3UaMI (B355-356.s
Keywords: (3GdLQGFe GdLfSjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3gJc GdYQVs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdRfGs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdSH hGdbPas -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdGZJUGHs -- (3bhGfjf hJTQjYGJs -- (3eUQs